Pasang Surut Otonomi Daerah Dalam Kerangka NKRI - Oktavia Pratiwi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
With the enactment of the autonomy law, local governments are given broader, real, and responsible authority in the administration of their government. The division of duties, functions, and roles between the central and regional governments requires each region to have sufficient income and adequate sources of financing to carry out its responsibilities. Regional autonomy provides freedom for regions to prepare programs and submit them to the central government. It is can have a positive impact and advance the area if the person or entity that prepares the program has good ability in planning the program and is able to analyze potential future events. However, the implementation of regional autonomy in Indonesia more or less adopts the concept of federalism, which can cause instability in Indonesia as a unified state.In the unitary state of the Republic of Indonesia, regions are not like states. Therefore, The application of regional autonomy within a unitary state is constrained by certain limitations.